The satanic epic - Forsyth, Neil, 1944- (Princeton University Press, 2003)
The Satan of Paradise Lost has fascinated generations of readers. This book attempts to explain how and why Milton's Satan is so seductive. It reasserts the importance of Satan against those who would minimize the poem's sympathy for the devil and thereby make Milton orthodox. Neil Forsyth argues that William Blake got it right when he called Milton a true poet because he was "of the Devils party" even though he set out "to justify the ways of God to men." In seeking to learn why Satan is so alluring, Forsyth ranges over diverse topics--from the origins of evil and the relevance of witchcraft t